From Diversity to Uniformity: A Study of "English for Academic Purposes" Courses in Community Colleges of Southern Ontario - Courtney, Lynn Diane (My University, 1995)
The community colleges were established in Ontario in 1965 during a period of economic optimism, characterized by a spirit of innovation and diversity. Growth and a willingness to experiment were the order of the day. One very positive outcome of these features was the freedom of opportunity for the colleges to develop autonomously and according to the needs of their particular community. This independence or lack of government direct involvement has changed rather dramatically since 1990, however. Pressures from the Ministry, for more systematic planning and centralized decision-making have been felt, initiated by the publication of Vision 2000. As a result, the former independent, innovative and diverse qualities of the colleges appear to be in jeopardy. Why this change in philosophy? Why at this time? What possible consequences might result? These are just two of the questions that will be discussed in the following project. A second and major portion of this project will trace the evolution, current status and future possibilities of one course in particular, English for Academic Purposes (EAP). This course or these courses were able to develop in the first place because the colleges had the opportunity for
Keywords: Community college; Diversity